Relaying the Epistemic Foundations of a Transcultural Natural Theology: Proving the Existence of God in Valignano’s Catechismus christianae fidei and Ruggieri’s Tianzhu shilu - Canaris, Daniel (Renaissance and Reformation / Renaissance et Réforme, 2021)
When European missionaries first entered Asia and the New World, they largely transposed to their new contexts European catechisms that assumed the intellectual passivity of the catechumen. The Jesuits, however, soon realized that such textual models would not be appropriate in East Asia which boasted its own sophisticated philosophical traditions. This article explores how Michele Ruggieri (1543–1607) deploys and adapts in his pioneering Chinese catechism, Tianzhu shilu 天主實錄 (The true record of the Lord of Heaven, 1584), innovations in the catechism genre that Jesuit missionaries had originally developed for Japan. By comparing Ruggieri’s arguments for the existence of God with those found in the Catechismus christianae fidei (Catechism of the Christian faith, 1586) composed by Alessandro Valignano (1539–1606) for the Japan mission, this article shows that Ruggieri lays the groundwork for a transcultural natural theology that de-emphasizes metaphysics in favour of arguments derived from a shared ethical understanding and political analogies.